2003
DOI: 10.1097/00005537-200307000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Pitch‐Raising Surgery in Fourteen Male‐to‐Female Transsexuals

Abstract: Pitch-raising surgery induces subjective and objective improvements but should be reserved for patients in whom speech therapy is not sufficiently effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
48
0
12

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 22 publications
0
48
0
12
Order By: Relevance
“…Fourteen male-to-female transsexuals who underwent cricothyropexy ± anterior commisure advancement were described by Wagner et al in 2003. 8 Voice parameters were assessed using electroglottography and speech therapy evaluation. Eleven patients experienced an improvement in F 0 (range, 9-114 Hz) and 11 patients expressed satisfaction with the results.…”
Section: Introductionmentioning
confidence: 99%
“…Fourteen male-to-female transsexuals who underwent cricothyropexy ± anterior commisure advancement were described by Wagner et al in 2003. 8 Voice parameters were assessed using electroglottography and speech therapy evaluation. Eleven patients experienced an improvement in F 0 (range, 9-114 Hz) and 11 patients expressed satisfaction with the results.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated the importance of speech-therapy services to transgender/transsexual individuals (Carew, Dacakis, & Oates, 2007;Davies & Goldberg, 2008;Hooper & Hershberger, 2012;McNeill, 2006;Pitts et al, 2009;Soderpalm, Larsson, & Almquist, 2004;Wagner, Fugain, Monneron-Girard, Cordier, & Chabolle, 2003). Some authors believe that an increase in awareness in the scope of practice of speech-language pathology among the LGBT population will result in an increase in the awareness of speech services and referrals from physicians (Soderpalm et al, 2004).…”
mentioning
confidence: 99%
“…Fig. 3 Mean F0 before and after surgery for vowel/a/ and text After cricothyroid approximation, the level of satisfaction ranges from 55 to 78 % [14,15]. Systematic evaluation of the satisfaction of M to F transgenders who underwent Wendeler's technique, or its modification has been usually done by applying the VHI questionnaire [7,8] We observed a mean VHI total score after procedure of 32, which is better than that found in previous studies, but remaining far from normal.…”
Section: Discussionmentioning
confidence: 99%